Nano Copper Sulfide-Doped nanofiber surface on polylactic acid substrate for advanced photothermal membrane distillation - Wang, Ao; Xu, Hang; Ma, Jun; Hu, Tianlong; Wang, Jingjun; Lin, Tao; Tao, Hui; Ding, Mingmei (Separation and purification technology, 2025)
[Display omitted] •An asymmetric construction for efficient PMD was proposed;•The PAPHF membrane maintained desalination efficiency with an daily flux of 1.86 kg·m−2·h−1;•CuS NPs decreased water-evaporation enthalpy in PMD process; The phase change process was simulated using CFD. Photothermal membrane distillation has been recognized as an attractive technology for freshwater generation. However, its widespread application still depends on substantial development to increase membrane flux and decrease energy consumption. Herein, we designed a electrospinning poly(vinylidene fluoride)–co-hexafluoropropylene (PVDF-HFP) nanofiber with photothermal CuS NPs as the top layer, while agglutinating the bottom hydrophilic polylactic acid layer by polydopamine, yielding a novel photothermal asymmetric PVDF-HFP fibrous (PAPHF) membrane. Compared to tradtional filtration method for material doped, such regulatable structure gives competitive advantage in the light utilization, water evaporation and transport. Electrospun photothermal nanofibers, which possesses a 81 %-90 % light-to-heat conversion efficiency, combined with the hydrophobic pores, can efficiently convert liquid water to vapor water and prevent heat diffusion outside the phase change inerface, meanwhile, enable effective vapor transport due to hydrophilic bottom layer with macropores. The PAPHF membrane demonstrated an excellent daily flux of 1.86 kg·m−2·h−1 with 1 sun irradiation as the only energy input. Computational fluid dynamics exhibited phase change processes acrosss the membrane. This study offers prospects for optimizing material combinations to improve performance, emphasizing scalable manufacturing implementation for broader applications.